PERAN HASIL TES PENJURUSAN STUDI TERHADAP PEMILIHAN JURUSAN PADA SISWA SMA - Esthi Wiji Sulystiyawati; Indriyati Eko Purwaningsih (Universitas Sarjanawiyata Tamansiswa, 2014)
ABSTRACTThis research aims: 1) To elicit major suggestion by Intelligenz Structure Test (IST); 2) To elicit major suggestion by Self Directed Search (SDS) results. 3) To find out role and effects the major placement test results to decide major preference for high school students.This research conducts Krectjie table as determination of sample numbers. The sample is the major placement test results which implemented to 396 high school students. They are 254 students from science majors and 142 from social majors. The research also applies random sampling method. Furthermore, the hypothetic test adapts non parametric analyzing technic of Chi Square.This research shows how significant differences between major suggestion from Intelligenz Structure Test (IST) results, Self Direct Search (SDS), and school recommendation. Proved by Chi-Square value at 222.173 with significance level 0.000 (0%) for frequency major suggestion differentiations from school recommendation, based on IST test. 32.536 with significance level 0.000 (0%) and 5.172 with significance level 0.023 (2.3%) for frequency major suggestion differentiations from school recommendation, based on SDS. 95.713 with significance level 0.000 (0%) and 149.414 with significance level 0.000 (0%) for frequency differentiation major suggestion by IST test from SDS test, also 221.90 and 45.306 with significance level 0.000 (0%) for frequency differentiation major suggestion based on placement test (IST and SDS) from school recommendation. Regarding to those results, show that there are some significant differences between school recommendation and test results. Those are not accidentally raise.Â Key words: Major Placement Test, Intelligenz Structure Test (IST), Self-Directed Search (SDS), Major Preferences, High School.